Carbohydrate recognition : biological problems, methods, and applications - Boons, Geert-Jan; Wang, Binghe , 1962- (Wiley series in drug discovery and development, 2011)
"This book contains contributions from interdisciplinary scientists to collectively address the issue of targeting carbohydrate recognition for the development of novel therapeutic and diagnostic agents. The book covers (1) biological problems involving carbohydrate recognition, (2) structural factors mediating carbohydrate recognition, (3) design and synthesis of lectin mimics that recognize carbohydrate ligands with high specificity and affinity, and (4) modulation of biological and pathological processes through carbohydrate recognition"--Provided by publisher.